Spore germination and young gametophyte development of the endemic Brazilian hornwort Notothylas vitalii Udar & Singh (Notothyladaceae - Anthocerotophyta), with insights into sporeling evolution - Bárbara Azevedo Oliveira; Anna Flora de Novaes Pereira; Kátia Cavalcanti Pôrto; Adaíses Simone Maciel-Silva (Acta Botânica Brasílica)
ABSTRACT Notothylas vitalii is an endemic Brazilian hornwort species, easily identified by the absence of pseudoelaters and columella, and the presence of yellow spores. Plant material was collected in Recife, Brazil, and the spores were sown onto Knop’s medium, germinating after thirty days only with the presence of light. Germination occurred outside the exospore, and only after the walls had separated into three or four sections did a globose sporeling initiate its development. Following longitudinal and transversal divisions, the initial loose mass of cells became a thalloid gametophyte, subsequently developing into a rosette-like juvenile thallus with flattened lobes. Additional information concerning sporeling types in key genera of hornworts, such as Folioceros and Phymatoceros, will be crucial for inferring the possible ancestral type and the evolution of this trait among hornworts. Our study supports the necessity of supplementary studies on sporeling development, combined with morphological and phylogenetic investigations, to help elucidate the evolution of the Anthocerotophyta and their distribution patterns.